The Birth of the Uruguayan Revolutionary Left, 1962-1967 - Rey Tristán, Eduardo (2002)
This work focuses on one of the most important and least known periods of the recent evolution of the left in Uruguay: the one that affects the key years of gestation of the revolutionary groups that, from 1968 until the 1973 coup d'état, played a fundamental role in the political and social evolution of the country of the Río de la Plata.